Current economic and environmental evaluation of solar power systems - Hollósy, Zsolt; Kiss, Lívia Benita; Juhász, Zita (Studia Mundi – Economica, 2021)
Investment decisions should be based on economic calculations because of their complexity and significant effect on the future. From the available and presented static and dynamic indicators calculation of the Net Present Value (NPV), the Discounted Cash Flow (DCF) as well as the Discounted Payback Period (DPP) made the choice between the different varieties easier. Subsidies and carbon price were taken into consideration and the equipment investment was evaluated in itself and its accounting and taxation relations as well. From 2016 to 2020, the unit's specific investment cost decreased significantly, and the examined indicators improved. They are further improvement by the advantageous location of installation. The reduction in CO2 emissions, that can be achieved with installed systems, depends significantly on the energy mix of the given country.